Five-step plasma-enhanced atomic layer etching of silicon nitride with a stable etched amount per cycle. (1st June 2022) - Hirata, Akiko; Fukasawa, Masanaga; Tercero, Jomar U.; Kugimiya, Katsuhisa; Hagimoto, Yoshiya; Karahashi, Kazuhiro; Hamaguchi, Satoshi; Iwamoto, Hayato
Abstract: Atomic layer etching is an advanced plasma etching technique that enables the atomic-precision control. In this study, the effects of surface conditions on the stability of the etched amount per cycle (EPC) in silicon nitride (SiN) plasma-enhanced atomic layer etching (PE-ALE) were examined. A single cycle of SiN PE-ALE consisted of two steps: hydrofluorocarbon (HFC) absorption step and argon-ion (Ar + ) desorption step. After a few cycles, an etch-stop of SiN occurred due to the HFC deposition. An oxygen-plasma ashing step was introduced after desorption step, which made three-step SiN PE-ALE. The etch-stop was avoided but the EPC was low due to the surface oxidation of SiN. By combining this three-step SiN PE-ALE with subsequent two-step SiO2 PE-ALE, which consists of fluorocarbon adsorption step and Ar + desorption step, SiN PE-ALE was achieved with a stable and large EPC. This five-step SiN PE-ALE allows the precise control of SiN etched depth.